MicroRNAs in Cancer Translational Research - Cho, William C.S (Springer Netherlands : Imprint: Springer, 2011)
MicroRNA (miRNA) is a cutting-edge topic in the scientific and medical fields. This is a timely and specialized book focusing on the current understanding of miRNAs and the potential for their application in cancer diagnosis, prognosis, and therapeutic targets. It also provides discussion of the lessons learned from translational miRNA studies and exploration of the next steps required to advance this field. The unique book comprises 22 in-depth chapters by gathering unparalleled topics of interest in miRNAs by international team of world-renowned experts in the field. The first fifteen chapters provide comprehensive and expert perspectives on the most common cancers from bench to bedside applications, there is no current book structured in this cancer-oriented way. The next seven chapters providing thorough overviews of miRNAs and cancer stem cells; miRNAs in cancer invasion and metastasis; miRNAs in predicting radiotherapy and chemotherapy response; as well as expounding the role of miRNA in anti-cancer drug resistance and as blood-based cancer biomarkers. Furthermore, this book explicates the interplay of miRNAs in cancer metabolism and an update on the pioneering RNAi-based treatment approaches is also presented. This specialized book will contribute great to the scientific and medical community by providing the up-to-date discoveries of miRNAs and their important roles in cancer translational research.